Fitonematodos asociados a las arecaceas en las antiguas provincias habaneras - Hung, M.L.=700 1 Gandarilla Basterrechea, H.; Reyes Laffita, L.
(Es, En)
Ilus., 11 ref.
Keywords: PALMAE; NEMATODOS DE LAS PLANTAS; PLANTAS ORNAMENTALES; CUBA